2015
DOI: 10.18632/oncotarget.3475
|View full text |Cite
|
Sign up to set email alerts
|

HSET overexpression fuels tumor progression via centrosome clustering-independent mechanisms in breast cancer patients

Abstract: Human breast tumors harbor supernumerary centrosomes in almost 80% of tumor cells. Although amplified centrosomes compromise cell viability via multipolar spindles resulting in death-inducing aneuploidy, cancer cells tend to cluster extra centrosomes during mitosis. As a result cancer cells display bipolar spindle phenotypes to maintain a tolerable level of aneuploidy, an edge to their survival. HSET/KifC1, a kinesin-like minus-end directed microtubule motor has recently found fame as a crucial centrosome clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 47 publications
7
99
1
Order By: Relevance
“…KIFC1 involves the growth of tumor and prognosis (18)(19)(20)(21)32), but these were based on clinical specimens. Our experiment is validated at a cellular level for the first time and the further explore the mechanisms was also first expounded.…”
Section: Discussionmentioning
confidence: 99%
“…KIFC1 involves the growth of tumor and prognosis (18)(19)(20)(21)32), but these were based on clinical specimens. Our experiment is validated at a cellular level for the first time and the further explore the mechanisms was also first expounded.…”
Section: Discussionmentioning
confidence: 99%
“…Protein lysates were prepared and immunoblotting was performed as described earlier. 19 Polyacrylamide gel electrophoresis was used to resolve the proteins, which were transferred onto polyvinylidene fluoride membranes (Millipore). The Pierce ECL chemiluminescence detection kit (Thermo Scientific) was used to visualize the immune-reactive bands.…”
Section: Immunohostochemistry Scoring and Weighted Index (Wi) Calcumentioning
confidence: 99%
“…It is reported that KIFC1 is abundantly and widely expressed in cancer cells of the ovary [22], breast [23], bladder [24], lung [25], kidney [26] and other cancers [26]. The special status of KIFC1 in cancer cells is, therefore, well established.…”
Section: Evidence For Applicability Of Kifc1-related Systems In Anti-mentioning
confidence: 99%
“…However, whilst many of the details of exactly how the elevated expression of KIFC1 occurs, remains unclear, part of the story, is beginning to be elucidated. The discovery, in breast cancer tissue, that the amplification of the KIFC1 gene relative to centromeres of chromosome 1 in breast cancer tissue gave the first hint as to why such a high expression of KIFC1 seems to be required in cancer cells [23]. …”
Section: Evidence For Applicability Of Kifc1-related Systems In Anti-mentioning
confidence: 99%
See 1 more Smart Citation